Handling Victims at the Badan Narkotika Nasional of North Sumatra Province through Fardiyah Da'wah - achiruddin hasibuan; syukur kholil; mailin mailin; rustono farady marta (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This study aims to describe the Islamiccommunication pattern of Badan Narkotika NasionalProvinsi Sumatera Utara/the National NarcoticsAgency of North Sumatra Province (BNNP-NorthSumatra) in order to prevent victims of narcoticsabuse in Medan City. The research also describes theobstacles experienced by BNNP-North Sumatra in aneffort to prevent victims of abuse This researchparadigm relies on constructivism with a qualitativeapproach and uses descriptive research, while theresearch method uses case studies. The results of thisstudy indicate that the BNNP of North Sumatra usesan Islamic communication pattern based on theanalysis of fardiyah da'wah, which also contains theprinciples of Islamic communication. The obstacleexperienced by the foundation while preventingvictims of drug abuse is the low self-restraint in thecommunity. The recovery process for victims of drugabuse at LRN (Lembaga Rehabilitasi Narkotika/Narcotics Rehabilitation Institute) Khalid Bin Walidas a rehabilitation center is through three stages ofrehabilitation, namely: pre-rehabilitation,rehabilitation process, and post-rehabilitation